The Growing Threat to Air Force Mission-Critical Electronics: Lethality at Risk: Unclassified Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
High-performance electronics are key to the U.S. Air Force2019s (USAF2019s) ability to deliver lethal effects at the time and location of their choosing. Additionally, these electronic systems must be able to withstand not only the rigors of the battlefield but be able to perform the needed mission while under cyber and electronic warfare (EW) attack. This requires a high degree of assurance that they are both physically reliable and resistant to adversary actions throughout their life cycle from design to sustainment. In 2016, the National Academies of Sciences, Engineering, and Medicine convened a workshop titled Optimizing the Air00a0Force00a0Acquisition Strategy of Secure and Reliable Electronic Components, and released a summary of the workshop. This publication serves as a follow-on to provide recommendations to the USAF acquisition community.

An Assessment of Selected Programs at the National Institute of Standards and Technology Engineering Laboratory: Fiscal Year 2020 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
National Institute of Standards and Technology (NIST) Engineering Laboratory has a long and distinguished record of technological leadership, innovation, and experience in providing analysis and solutions to large and small problems. Engineering Laboratory research quality is exemplified by the programs' science-based tools and outputs. This report assesses the scientific and technical work performed by the NIST Engineering Laboratory and presents findings, conclusions, and recommendations to advance the mission and vision of NIST with a focus on strategic thinking and planning to support long-term efforts.

Energizing Data-Driven Operations at the Tactical Edge: Challenges and Concerns - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Significant efforts are ongoing within the U.S. Air Force (USAF) to improve national security and competitiveness by harnessing the growing power of information technologies, such as artificial intelligence (AI) and robotics. Product and process technologies are being researched, experimented with, and integrated into future warfighting concepts and plans. A significant part of this effort is focused on integrating operations, from the strategic to the tactical and across all lines of effort. A question that must be asked in considering these future warfighting concepts is: how will the devices that enable the knowledge-based future be powered? The abundant energy supplies that characterize peacetime operating environments may not be readily available at the far reaches of the force projections - the tactical edge - during conflict. Understanding the energy challenges associated with continued data collection, processing, storage, analysis, and communications at the tactical edge is an important part of developing the plans for meeting the future competition on the battlefield. This report identifies challenges and issues associated with energy needs at the tactical edge as well as any potential for solutions to be considered in the future to help address these challenges. The recommendations of Energizing Data-Driven Operations at the Tactical Edge address understanding these requirement needs and the cascading effects of not meeting those needs, integrating energy needs for data processing into mission and unit readiness assessments, and research into product and process technologies to address energy-efficient computation, resilience, interoperability, and alternative solutions to energy management at the tactical edge.

Attracting, Recruiting, and Retaining Skilled Staff for Transportation System Operations and Management - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2012)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 693: Attracting, Recruiting, and Retaining Skilled Staff for Transportation System Operations and Management provides guidance designed to help transportation agencies recruit and retain qualified professional staff in the systems operation and management (SOM) area.The report explores SOM career paths, skill requirements, and training needs and identifies successful programs, state-of-the-art initiatives, and best industry practices.A set of tables showing SOM job categories, number of positions, and educational requirements for all 50 states was published as NCHRP Web-Only Document 182: Appendices to NCHRP Report 693.In addition, a summary of the results of the project that developed NCHRP Report 693 and suggestions for senior management personnel related to attracting, recruiting, and retaining skilled staff for transportation system operations and management are available in an online Executive Workbook.

Equipping Tomorrow's Military Force: Integration of Commercial and Military Manufacturing in 2010 and Beyond - National Research Council (The National Academies Press, 2002)
Owing to the expected nature of combat in 2010, U.S. military forces face a pressing need to transform themselves for rapid response to an unpredictable threat. Rapid advances in commercial technology (particularly in electronics), coupled with the easy access to commercial technology enjoyed by potential adversaries, will compel DOD and defense contractors to excel at integrating commercial technology into defense systems. This integration of commercial and military manufacturing (ICMM) has begun on a small scale. By 2010, it needs to increase substantially if U.S. forces are to retain a technological edge. This report assesses the opportunities for increased ICMM in 2010 and beyond, identifies barriers, and recommends strategies for overcoming them.

An Assessment of the National Institute of Standards and Technology Chemical Science and Technology Laboratory: Fiscal Year 2009 - National Research Council
An Assessment of the National Institute of Standards and Technology Chemical Science and Technology Laboratory examines the operations of the Chemical Science and Technology Laboratory (CSTL) of the National Institute of Standards and Technology (NIST). This book assesses the CSTL, based on the following criteria: (1) the technical merit of the current laboratory programs relative to current state-of-the-art programs worldwide; (2) the adequacy of the laboratory budget, facilities, equipment, and human resources, as they affect the quality of the laboratory's technical programs; and (3) the degree to which laboratory programs in measurement science and standards achieve their stated objectives and desired impact.\

From Molecules to Minds: Challenges for the 21st Century: Workshop Summary - Institute of Medicine
Neuroscience has made phenomenal advances over the past 50 years and the pace of discovery continues to accelerate. On June 25, 2008, the Institute of Medicine (IOM) Forum on Neuroscience and Nervous System Disorders hosted more than 70 of the leading neuroscientists in the world, for a workshop titled \

Building Consensus Through Risk Assesment and Management of the Department of Energy's Environmental Remediation Program (The National Academies Press, 1994)

Adapting to Shorter Time Cycles in the United States Air Force: Proceedings of a Workshop Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The Air Force Studies Board of the National Academies of Sciences, Engineering, and Medicine hosted a three-part workshop series to investigate the changing paradigm of time and knowledge in modern-day warfare. Sponsored by the U.S. Department of Defense, three 2-day workshops were held virtually on September 16-17, 2020, September 23-24, 2020, and October 1-2, 2020. The objective of the first workshop was to explore the ways in which the U.S. Air Force (USAF) has adjusted its capabilities in response to past shifts in operational timing. In consideration of these past shifts, the second workshop aimed to consider when there could be an advantage to synchronize or desynchronize rates of change with adversaries. Participants had the opportunity to discuss lessons learned and possible changes for USAF Doctrine and future operations. The goal of the third workshop was to examine the implications to doctrine, concepts of operations, and command and control from the recent acceleration of battlespace operations, arising from wide-scale digitization, large-scale sensing, and faster technologies. In all three workshops, speakers explored the broader issues surrounding changing environments, and participants discussed ways to adapt to fundamental changes in the time constants of conflict. This proceedings is a factual summary of what occurred during the workshop series.

From Earth to Orbit: An Assessment of Transportation Options - National Research Council (The National Academies Press, 1992)
If the United States hopes to continue as a leader in space, it must invest now in better earth-to-orbit technology by replacing obsolete launch facilities while also developing a new class of more robust and reliable vehicles. From Earth to Orbit provides strategies to reduce launch costs while increasing the reliability and resiliency of vehicles. It also recommends continued improvements for the Space Shuttle Orbiter and its subsystems and the development of a Space Transportation Main Engine (STME).

Future Air Force Needs for Survivability - National Research Council (The National Academies Press, 2006)
A key technical issue for future Air Force systems is to improve their ability to survive. Increased use of stealth technology is proposed by many to be the major element in efforts to enhance survivability for future systems. Others, however, suggest that the high cost and maintenance required of stealth technology make increased speed potentially more productive. To help address this issue, the Air Force asked the NRC to investigate combinations of speed and stealth that would provide U.S. aircraft with a high survival capability in the 2018 period, and to identify changes in R&D plans to enable such aircraft. This report presents a review of stealth technology development; a discussion of possible future missions and threats; an analysis of the technical feasibility for achieving various levels of stealth and different speeds by 2018 and of relevant near-term R&D needs and priorities; and observations about the utility of speed and stealth trade-offs against evolving threats.

Nineteenth Interim Report of the Committee on Acute Exposure Guideline Levels: Part A - National Research Council (The National Academies Press, 2011)
The present report is the committee's 19th interim report. It summarizes the committee's conclusions and recommendations for improving NAC's AEGL documents for the following chemicals and chemical classes: acrylonitrile, benzonitrile, boron tribromide, BZ (3-quinuclidinyl benzilate), chloroarsenicals, chloroformates, bis-chloromethylether, chloromethylether, chlorosilanes (26 selected compounds), cyanogen, ethyl mercaptan, hexafluoroacetone, lewisites, mercury vapor, nitric acid, nitric oxide, nitrogen dioxide, nitrogen tetroxide, oleum, phenyl mercaptan, propargyl alcohol, selenium hexafluoride, silane, sulfer trioxide, sulfuric acid, tear gas, tert-octyl mercaptan, tetramethoxy silane, thionyl chloride, trimethoxysilane, trimethylbenzenes (1,2,4-; 1,2,5-;and 1,3,5-TMB), and vinyl chloride.

Twentieth Interim Report of the Committee on Acute Exposure Guideline Levels: Part A - National Research Council (The National Academies Press, 2011)
Extremely hazardous substances (EHSs) can be released accidentally as a result of chemical spills, industrial explosions, fires, or accidents involving railroad cars or trucks transporting EHSs. They can also be released intentionally through terrorist activities, or inadvertently by improper storage or handling. Workers and residents in communities surrounding industrial facilities where EHSs are manufactured, used or stored, and in communities along the nation's railways and highways, are potentially at risk of being exposed to airborne EHSs during accidental or intentional releases. The Twentieth Interim Report of the Committee on Acute Exposure Guideline Levels: Part A presents conclusions and recommendations for improving the National Advisory Committee (NCA) on Acute Exposure Guideline Levels (AEGL) documents for the various twenty-nine chemicals and chemical classes, among them being chloroacetyl chloride, butane, ethyl, and nitrogen mustards. In addition to providing advisory data, the interim report reviews the proposed AEGLs for scientific validity, completeness, internal consistency, and conformance to prior National Research Council guideline reports. The report reviews NAC's research recommendations and-when appropriate-identifies additional priorities for research to fill data gaps. Moreover, this all-inclusive report provides updated technical guidance for establishing community emergency exposure levels for extremely hazardous substances pursuant to the Superfund Amendments and Reauthorization Act of 1986.

Recommended Procedures for Testing and Evaluating Detectable Warning Systems - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 670: Recommended Procedures for Testing and Evaluating Detectable Warning Systems explores a set of recommended test methods for evaluating the durability of detectable warning systems. These methods address exposure regimes, test procedures, and evaluation criteria to help select detectable warning systems that provide long-term performance and durability while meeting the requirements of the Americans with Disabilities Act Accessibility Guidelines.The appendix contained in the research agency2019s final report provides further elaboration on the work performed in this project. This appendix titled Research Leading to the Development of Methodology for Durability Assessment of Detectable Warning Systems is available online.

Trip Generation Rates for Transportation Impact Analyses of Infill Developments - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2013)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 758: Trip Generation Rates for Transportation Impact Analyses of Infill Developments details a procedure for analyzing potential vehicular trip generation impacts in urban and urbanizing locales.

Recommended Guidelines for the Collection and Use of Geospatially Referenced Data for Airfield Pavement Management - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s Airport Cooperative Research Program (ACRP) Report 39: Recommended Guidelines for the Collection and Use of Geospatially Referenced Data for Airfield Pavement Management offers recommended guidelines for the collection and use of geospatially referenced data for airfield pavement management.The guidelines provide a data schema, data collection methods, data quality requirements, and other relevant information required for developing specifications and standards for integrating geospatial data into pavement management systems. Appendixes A through C to ACRP Report 39 are available online. Titles of the appendixes are as follows:2022 Appendix A: Survey Questionnaire2022 Appendix B: Questionnaire Responses2022 Appendix C: Pavement Management Systems Software Data Elements

The Role of Environmental NGOs: Russian Challenges, American Lessons: Proceedings of a Workshop - National Research Council (The National Academies Press, 2001)
An NRC committee was established to work with a Russian counterpart group in conducting a workshop in Moscow on the effectiveness of Russian environmental NGOs in environmental decision-making and prepared proceedings of this workshop, highlighting the successes and difficulties faced by NGOs in Russia and the United States.

Aging Avionics in Military Aircraft - National Research Council (The National Academies Press, 2001)
Extending the life of an airframe has proven challenging and costly. Extending the life of an avionics system, however, is one of the most critical and difficult aspects of extending total aircraft system lifetimes. Critical components go out of production or become obsolete, and many former suppliers of military-grade components have gone out of business. From 1986 to 1996, for example, the percentage of discontinued military\/aerospace electronic devices nearly doubled2014from 7.5 percent to 13.5 percent. In addition, legacy avionics systems, which were designed to meet requirements of the past, generally lack the full capability to perform new missions, meet new threats, or perform well in the new information-intensive battlefield environments. As the legacy aircraft fleet ages, avionics systems will become more and more difficult to support and maintain. Whereas the military once provided a large and profitable market for the electronics industry, the military electronics market today constitutes less than 1 percent of the commercial market. As a result, the military must increasingly rely on commercial off-the-shelf (COTS) technologies for its avionics hardware and software. Although COTS items are generally less expensive than comparable items designed especially to meet military specifications, the technology-refresh cycle for COTS is typically 18 months or less, which exacerbates the obsolescence problem for aircraft whose lifetimes are measured in decades. The short refresh cycle is driven mostly by the tremendous advances in computer systems, which comprise an increasing percentage of avionics content. In response to a request by the Assistant Secretary of the Air Force for Acquisition, the National Research Council convened the Committee on Aging Avionics in Military Aircraft, under the auspices of the Air Force Science and Technology Board, to conduct this study. This report summarizes the following: Gather information from DoD, other government agencies, and industrial sources on the status of, and issues surrounding, the aging avionics problem. This should include briefings from and discussions with senior industry executives and military acquisition and support personnel. A part of this activity should include a review of Air Force Materiel Command's study on diminishing manufacturing sources to recommend ways to mitigate avionics obsolescence. Provide recommendations for new approaches and innovative techniques to improve management of aging avionics, with the goal of helping the Air Force to enhance supportability and replacement of aging and obsolescing avionics and minimize associated life cycle costs. Comment on the division of technology responsibility between DoD and industry.

America's Future in Space: Aligning the Civil Space Program with National Needs - National Research Council (The National Academies Press, 2009)
As civil space policies and programs have evolved, the geopolitical environment has changed dramatically. Although the U.S. space program was originally driven in large part by competition with the Soviet Union, the nation now finds itself in a post-Cold War world in which many nations have established, or are aspiring to develop, independent space capabilities. Furthermore discoveries from developments in the first 50 years of the space age have led to an explosion of scientific and engineering knowledge and practical applications of space technology. The private sector has also been developing, fielding, and expanding the commercial use of space-based technology and systems. Recognizing the new national and international context for space activities, America's Future in Space is meant to advise the nation on key goals and critical issues in 21st century U.S. civil space policy.

A Methodology for Performance Measurement and Peer Comparison in the Public Transportation Industry - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2010)
TRB2019s Transit Cooperative Research Program (TCRP) Report 141: A Methodology for Performance Measurement and Peer Comparison in the Public Transportation Industry explores the use of performance measurement and benchmarking as tools to help identify the strengths and weaknesses of a transit organization, set goals or performance targets, and identify best practices to improve performance.